Frictional Melting in Hydrothermal Fluid‐Rich Faults: Field and Experimental Evidence From the Bolfín Fault Zone (Chile). (12th July 2021) - Gomila, R.; Fondriest, M.; Jensen, E.; Spagnuolo, E.; Masoch, S.; Mitchell, T. M.; Magnarini, G.; Bistacchi, A.; Mittempergher, S.; Faulkner, D.; Cembrano, J.; Di Toro, G.
Abstract: Tectonic pseudotachylytes are thought to be unique to certain water‐deficient seismogenic environments and their presence is considered to be rare in the geological record. Here, we present field and experimental evidence that frictional melting can occur in hydrothermal fluid‐rich faults hosted in the continental crust. Pseudotachylytes were found in the >40 km‐long Bolfín Fault Zone of the Atacama Fault System, within two ca. 1 m‐thick (ultra)cataclastic strands hosted in a damage‐zone made of chlorite‐epidote‐rich hydrothermally altered tonalite. This alteration state indicates that hydrothermal fluids were active during the fault development. Pseudotachylytes, characterized by presenting amygdales, cut and are cut by chlorite‐, epidote‐ and calcite‐bearing veins. In turn, crosscutting relationship with the hydrothermal veins indicates pseudotachylytes were formed during this period of fluid activity. Rotary shear experiments conducted on bare surfaces of hydrothermally altered rocks at seismic slip velocities (3 m s −1 ) resulted in the production of vesiculated pseudotachylytes both at dry and water‐pressurized conditions, with melt lubrication as the primary mechanism for fault dynamic weakening. The presented evidence challenges the common hypothesis that pseudotachylytes are limited to fluid‐deficient environments, and gives insights into the ancient seismic activity of the system. Both field observations and experimental evidence, indicate that pseudotachylytes may easily be produced in hydrothermal environments, and could be a common co‐seismic fault product. Consequently, melt lubrication could be considered one of the most efficient seismic dynamic weakening mechanisms in crystalline basement rocks of the continental crust. Key Points: The Bolfín Fault Zone shows the first pseudotachylytes described in the Atacama Fault System giving insights of past seismic activity Rotary shear experiments at seismic slip velocities resulted in formation of vesiculated pseudotachylytes in all tested conditions Natural pseudotachylytes formed in a hydrothermal fluid‐rich environment where vesiculation is related to CO2 degassing from calcite veins